Similarities and differences between two different types of the thermoluminescence dosimeters belonging to the LiF family. Issue 1 (30th November 2016) - Sadek, A. M.; Khamis, F.; Polymeris, George S.; Carinou, E.; Kitis, G.
Abstract : The kinetic parameters of the glow‐peaks of Harshaw – LiF:Mg, Ti (TLD) and Poland – LiF:Mg, Ti (MTS) dosimeters were investigated at different dose levels using the computerized glow‐curve deconvolution (CGCD) algorithm. The results showed that the glow‐curve structure and the kinetic parameters of the MTS – 6 and the TLD dosimeter are identical. In addition, the glow‐curve structure and the kinetic parameters of the MTS – N and MTS – 7 dosimeters. However, unusual low activation energy (∼1.67 eV) and frequency factor (∼10 15 s –1 ) values were detected for peak 5 of MTS – N, and MTS – 7 at the 50 Gy dose‐level. Moreover, unlike the activation energy and the frequency factor of peak 5 of the TLD dosimeters, the activation energy and the frequency factor of peak 5 of MTS – N and MTS – 7 are substantially dependent on the absorbed dose level. The results also showed that peak 2 of the same dosimeters has also unusual low activation energy and frequency factor values. However, these values showed high stability over the different dose levels. The explanations of these unusual behaviors of peak 5 were discussed and a correlation between peak 2 and peak 5 was pointed out.